A high molar activity 18F-labeled TAK-875 derivative for PET imaging of pancreatic β-cells - Mark H. Dornan; Daniil Petrenyov; José-Mathieu Simard; Antonio Aliaga; Guoming Xiong; Julien Ghislain; Barry Bedell; Vincent Poitout; Jean N. DaSilva (SpringerOpen, 2018)
Abstract Background The free-fatty acid receptor-1 (FFA-1) is expressed by β-cells and is a promising target for molecular imaging of functional β-cell mass. Recently, the ((3-[18F]fluoropropyl)sulfonyl)propoxy-derivative of the high-affinity FFA-1 agonist TAK-875 ([ 18 F]7) was reported. Here we describe the preparation of this tracer in high molar activity using a purification method permitting separation of [ 18 F]7 from a structurally-related by-product and evaluation of the tracer in rats as a potential FFA-1 PET imaging agent. Results The radiotracer was produced by nucleophilic radio-fluorination of the tosylate precursor and deprotection of the methyl ester. Semi-preparative HPLC with a C18 column revealed that [ 18 F]7 co-eluted with a non-radioactive impurity. Mass spectrometry identified the impurity as the alkene-containing elimination by-product. A pentafluorophenyl-functionalized HPLC column was found to separate the two compounds and allowed for purification of [ 18 F]7 in high molar activity. A strong anion-exchange resin was used to reformulate [ 18 F]7 in high concentration. Starting from 96 to 311 GBq of [18F]fluoride, 3.8-15.4 GBq of pure [ 18 F]7 (end of synthesis (EOS)) was prepared (RCY 8.3% ± 1.1% decay-corrected, n = 4) in high molar activity (166-767 GBq/μmol at EOS). This PET agent was evaluated in rats using dynamic microPET/CT imaging, ex vivo biodistribution, and radio-metabolite studies. MicroPET/CT exhibited high uptake of the tracer in the abdominal area. There was no measurable decrease of the PET signal in the pancreatic area in rats pre-treated with saturating doses (30 mg/kg) of TAK-875. Biodistribution studies corroborated the microPET/CT results. Radiometabolism analyses revealed high compound stability with only the parent molecule detected in the pancreas. Conclusions Analysis of the crude reaction mixture and identification of the elimination by-product allowed for the development of a fully automated process to prepare the TAK-875-derived PET agent [ 18 F]7 in high purity and high molar activity. Even though the radiotracer exhibited high in vivo stability, microPET/CT and biodistribution results confirmed recent reports demonstrating that lipophilic analogs of TAK-875 display a high degree of non-specific binding, masking any specific binding to FFA-1 in pancreatic β-cells. Future development of TAK-875-derived PET tracers should focus on reducing non-specific binding in the pancreatic tissue.